Group Perceptions of Acceptance of Racial/Ethnic, Sexual and Gender Minorities in the United States Military. (3rd April 2021) - Green, Daniel C.; Holloway, Ian W.; Pickering, Chad E.; Tan, Diane; Tzen, Michael; Goldbach, Jeremy T.; Castro, Carl A.
Abstract: Recruitment of soldiers from diverse backgrounds has increasingly become a priority for the U.S. military. Although there has been success in recruiting a more diverse and representative military workforce, perceptions of acceptance of minority military personnel remains underexplored. The present study sought to measure perceptions of acceptance among active-duty military personnel with diverse backgrounds by comparing perceived levels of acceptance both in and outside minority group membership among racial and ethnic, gender, and sexual minority-identifying participants. Results suggest members of minority groups tended to perceive lower acceptance of both their minority group and other minority groups compared with their perceptions of acceptance of majority groups. In particular, White, heterosexual, cisgender males tended to perceive minority groups as more accepted than those in minority groups perceived themselves. These results suggest the implementation of programs designed to improve workplace climate and awareness of diversity and equity issues may be beneficial.